SMEs Halal Culinary Strategy During The Pandemic Era In South Tangerang - Marissa Grace Haque; Nuraeni; Rifzaldi Nasri (Jurnal Manajemen, 2022)
The aim of this study is to see and to analyze what type of business strategies should be implemented to the halal-certified culinary SMEs named “Nasi Kebuli Bang Moch.” This study uses mixed-method approaches, equipped with its descriptive analysis. The measuring tool used is a SWOT analysis (strengths, weaknesses, opportunities, threats), through the "Internal-External" weighting step, then equipped with a "Four-Step Strategy", in order to be able to determine the most efficient and effective strategy needed. In addition, to the strengths of its company and to achieve the expected sustainable business management, due to the result of the study which shows several weaknesses to be able to capture opportunities while at the same time dealing with threats, digital marketing and product variant innovation, becomes inevitable. Furthermore, its "cost leadership strategy" that had previously been implemented, must be maintained. To sum up, Nasi Kebuli Bang Moch halal SMEs business can continue to be sustainable, by adapting all developments of digital world businesses as well as its product innovation, at any situation and condition.